Assessing Equipment, Supplies, and Devices for Patient Safety Issues - Raj M. Ratwani; Katharine T. Adams; Tracy C. Kim; Deanna-Nicole C. Busog; Jessica L. Howe; Rebecca Jones; Seth Krevat (Patient Safety)
# Background